Adding Hydrochlorothiazide to Olmesartan/Amlodipine Increases Efficacy in Patients With Inadequate Blood Pressure Control on Dual‐Combination Therapy. Issue 1 (14th July 2015) - Rump, Lars C.; Ammentorp, Bettina; Laeis, Petra; Scholze, Jürgen
Abstract : This randomized, parallel‐group study in patients inadequately controlled on olmesartan medoxomil/amlodipine (OLM/AML) 40/10 mg assessed the effects of adding hydrochlorothiazide (HCTZ) 12.5 mg and 25 mg, using seated blood pressure (SeBP) measurements and ambulatory blood pressure (BP) monitoring. Enrolled patients were screened and tapered off of therapy if required. All patients received OLM/AML 40/10 mg and those with mean seated BP (SeBP) ≥140/90 mm Hg after 8 weeks (n=808) were randomized (1:1:1) to continue with OLM/AML 40/10 mg or receive OLM/AML/HCTZ 40/10/12.5 or 40/10/25 mg for a further 8 weeks. The primary endpoint was the change in seated diastolic BP (SeDBP) from the start to the end of the randomized treatment period. The addition of HCTZ 25 mg significantly reduced SeDBP (−2.8 mm Hg; P <.0001), lowered seated systolic BP (SeSBP) and ambulatory DBP and SBP, and improved BP goal rates. In patients uncontrolled on OLM/AML 40/10 mg, adding HCTZ led to further BP reductions, particularly in ambulatory BP.